Animal performance changes related to time on feed - Chestnut, A.; Brent, B.E. (Kansas State University. Agricultural Experiment Station, 2011)
We are developing mathematical models to show how feed intake, rate of gain, and feed efficiency change during the finishing period. When finished, the models might be used to predict when to sell cattle to maximize profit or minimize loss, to plan feed inventories, or to predict when animals have reached a desired grade.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Animal performance; Feed intake; Rate of gain; Feed efficiency